An exploratory study of information avoidance behavior of undergraduate students in monitoring their academic goal progress - Baxa, Patricia Marie L. (2022)
Background. Much of the literature on information behavior explores information seeking. Active acquisition of information is attributed to knowledge and certainty, whereas avoidance is perceived as counter to the norm of information seeking. However, information avoidance can be considered rational behavior in certain situations. Objective. This study explored avoidance behavior in the context of academic goal progress. Avoidance behavior is manifested when students procrastinate and delay obtaining reports on academic progress from their professors. Method. The study participants were 44 Bachelor of Library and Information Science students at the University of the Philippines Diliman, who filled out a questionnaire. The questionnaire was adapted from Addison (2017) and Dr. Freund’s Affect and Avoidance study design that examined avoidance in the context of personal health concerns. A pretest was conducted and the results used in modifying the questionnaire. Results. Through quantitative analysis, it was found that avoidance of academic progress information was not prevalent among the students. Most students sought information on their progress and status with respect to their academic goals. When they did avoid it, it was to prevent distressing emotions. However, many students were willing to accept inconvenient truths about their performance Implications. By the end of the study, inferences about information-seeking behaviors concerning goal progress that the students do not observe can be known. This will assist teachers and universities to find ways to help students monitor their academic goal progress.